2019
DOI: 10.1007/s40314-019-0880-y
|View full text |Cite
|
Sign up to set email alerts
|

A reduced-order extrapolated natural boundary element method based on POD for the parabolic equation in the 2D unbounded domain

Abstract: In this article, we devote ourselves to the research of order reduction of natural boundary element (NBE) based on a proper orthogonal decomposition (POD) for the parabolic equation in the two-dimensional (2D) unbounded domain. For this purpose, we first build a NBE format for the parabolic equation in the 2D unbounded domain and discuss the existence, stability, and convergence of the NBE solutions. And then, we build a reduced-order NBE extrapolated (RONBEE) format based on POD, analyze the errors between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Provided that it is applied for settling big data processing in artificial intelligence and/or computational linguistics, there will be more than tens of millions unknown numbers. Fortunately, a proper orthogonal decomposition (POD) technique may be used to reduce the unknowns in the CNFE method, which can be used to reduce many numerical methods (see, e.g., [17][18][19][20][21][22]). Our future work is reducing the number of unknowns in the CNFE method by the POD technique.…”
Section: Conclusion and Expectationmentioning
confidence: 99%
“…Provided that it is applied for settling big data processing in artificial intelligence and/or computational linguistics, there will be more than tens of millions unknown numbers. Fortunately, a proper orthogonal decomposition (POD) technique may be used to reduce the unknowns in the CNFE method, which can be used to reduce many numerical methods (see, e.g., [17][18][19][20][21][22]). Our future work is reducing the number of unknowns in the CNFE method by the POD technique.…”
Section: Conclusion and Expectationmentioning
confidence: 99%
“…Hence, it is necessary to study the TGCNFE method for the unsaturated soil flow equation. A significant amount of numerical simulations (see [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]) have revealed that the POD method plays an important role in lessening the unknowns of numerical models and has been successfully used in various fields, such as fluid mechanics and atmospheric sciences (see [34]), statistics (see [35]), and image recognition and signal processing (see [36]).…”
Section: Introductionmentioning
confidence: 99%
“…It was not until 2001 that the POD method was used to concern with the reduced-order of the Galerkin method for the parabolic type PDEs and to discuss the error estimates of the reduced-order Galerkin solutions ( [11]). The POD method is used to the reduced-order for the classical numerical methods such as the finite difference schemes ( [12][13][14]), the FE methods ( [15][16][17]), the finite volume element (FVE) methods ( [18,19]), the collocation spectral (CS) methods ( [20,21]), and the natural boundary element (NBE) method ( [22,23]). It is also used in the reduced basis methods ( [24,25]).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the reduced-order Galerkin methods in [11,26,27], the reduced-order FE methods in [15,17], the reduced-order FVE methods in [18,19], the reduced-order CS methods in [20,21], the reduced-order NBE methods in [22,23] and the reduced basis methods in [24,25] are constructed by the continuous POD basic functions. The constructing process of the continuous POD basic functions requires the knowledge of the optimization methods and functional analysis.…”
Section: Introductionmentioning
confidence: 99%